The Added Value of Knowledge Management in the Operation of Public Organizations (International Journal of Scientific Research and Management (IJSRM), 2022)
This paper attempts to outline the role of knowledge management in the public sector and the way it contributes to its operation, creating added value. Modern public organizations face significant challenges in the knowledge economy and must constantly adapt to the economic, social, and cultural changes of the environment. In this context, they must adopt new standards, that put the management of their intangible assets at the core of their strategies. Recognizing the vital role of knowledge resources in guiding public organizations can lead to better performance. The peculiar nature of these organizations, however, seems to create obstacles to knowledge management efforts, as these organizations tend to be highly bureaucratic and trapped in rigid hierarchies, and require knowledge management strategies that are able to deal with this situation. The conclusions of this paper are based on the results of secondary research conducted through an extensive review of international and Greek literature and articles, as well as research in digital sources of information, and highlight the added value of knowledge management in the public sector.